Стратегийн болон боломжит стратегийн ордуудыг матрицын шинжилгээний аргаар үнэлсэн үнэлгээний дүн - Э.Эрдэнэчимэг,; Н.Мөнхбилэг,; З.Ганбаатар,; Б.Асралт, (Geological Issues, 2023)
This study was aimed for "The development of proposals for improving the current legal and regulatory framework of the mineral resource sector, to determine the current and future trends in commodity markets, to propose which mines to prioritize on development on the basis of the current state of development of the industry". The study goals are: 1.A general overview of the Mongolian socio-economic status and especially the role of the mining sector within the economy: 2.An overall mineral resource commodity study on the current global, regional and neighbouring country markets and their trends: 3.A study for the reserve, extraction, production and beneficiation of mineral resource commodities based on strategic and potential strategic deposits and their mineral classifications: 4.To identify the top priority mines and deposits from the strategic and potential strategic deposits by the SWOT matrix analysis methodology: To study the current Mongolian legal and regulatory framework on the mineral resource sector and to ultimately provide feedback and proposal to further the improvement and development of the mineral resource sector.